1996
DOI: 10.1159/000129469
|View full text |Cite
|
Sign up to set email alerts
|

Body Composition and Energy Expenditure in Obese Patients prior to and following Biliopancreatic Diversion for Obesity

Abstract: Body composition and resting energy expenditure (REE) were assessed in 69 obese patients prior to and 1 year following biliopancreatic diversion (BPD). Fat-free mass (FFM) and body fat sizes were very similar to those of nonoperated subjects closely matched for body weight and FFM size. In the BPD subjects, the REE data were high, thus excluding a dilatation of non-energy-consuming extracellular spaces and suggesting an increase in the ratio between the organs and the less metabolically active muscle mass with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…This demonstrates that the lipid content of the adipocytes was greatly decreased following surgery. Adami et al 22 found that 80% of the first postoperation weight loss in human subjects with BPD was due to an FM loss. The reducing effect of the BPD on FM deposition was more noticeable than the effect of the surgery on the FFM, which was nonetheless also reduced.…”
Section: Discussionmentioning
confidence: 99%
“…This demonstrates that the lipid content of the adipocytes was greatly decreased following surgery. Adami et al 22 found that 80% of the first postoperation weight loss in human subjects with BPD was due to an FM loss. The reducing effect of the BPD on FM deposition was more noticeable than the effect of the surgery on the FFM, which was nonetheless also reduced.…”
Section: Discussionmentioning
confidence: 99%
“…Weight loss in rodent models of RYGB is associated with preservation of lean body mass and increased EE [ 146 ]. Humans have decreased basal metabolic rate, but increased meal-induced thermogenesis after RYGB [ 32 , 122 , 147 153 ]. Evidence is now also emerging to suggest that the metabolic rate of the small bowel is increased after RYGB with more carbohydrate consumption which may explain the changes observed in respiratory quotient after these operations [ 154 ].…”
Section: Energy Expenditurementioning
confidence: 99%
“…This results in a life-long threshold energy absorption that explains the life-long weight maintenance after the procedure [4]. An additional mechanism that ulteriorly lowers the weight of stabilization is the increased resting energy expenditure due to the adaptive hypertrophy of the entire highly consuming small bowel [5].…”
Section: The Operation and Its Mechanisms Of Actionmentioning
confidence: 99%